Early detection of skin and cardiac amyloid deposits among asymptomatic carriers of hereditary pathogenic transthyretin mutation with normal electroneuromyography. (25th November 2020) - Slama, M; Eliahou, L; Piekarski, E; Rouzet, F; Beauvais, D; Beaudonnet, G; Labeyrie, C; Cauquil, C; Adams, D; Algalarrondo, V
Abstract: Introduction: During the last decade, disease modifying therapies have been proposed for hereditary amyloidogenic transthyretin (ATTRv) amyloidosis. It is essential to screen for disease onset among asymptomatic mutation carriers in order to trigger effective therapy as early as possible. We describe clinical and paraclinical data from ATTRv asymptomatic carriers, as a baseline assessment to detect disease onset and progression. Methods: We retrospectively collected data of asymptomatic ATTRv carriers with normal electroneuromyography (ENMG), between March 1st 2015 and January 31st 2019, including: demographics, symptoms, physical exam, ENMG (initial and follow-up obtained in 73 patients, 56.2%), neurovegetative tests, skin biopsy (amyloid deposition, denervation), and cardiac evaluation (multimodal imaging, cardiac denervation and arrhythmias). Results: We included 130 patients, aged 43.6 years (± 13.5), selected in family of a proband with an age of onset of 52.7 years (±15.7), 40.8% male, carrying 20 different variants of the TTR gene, including 63.8% Val30Met. Amyloid deposits on skin biopsy and/or cardiac fixation on bone scintigraphy, characteristic of amyloid infiltration, were found in 22/130 patients (16%). Skin biopsy was positive in 11 patients, and cardiac fixation on bone scintigraphy was positive in 15 patients. Amyloid infiltration was statistically associated with age (p=0.024), age difference from index case (p<0.001), electrophysiological carpal tunnel syndrome (p=0.022), interventricular septum thickness >12 mm (p<0.001), contrast enhancement in cardiac MRI (p=0.002), cardiac denervation using MIBG scintigraphy C/M ratio <1.85 (p=0.044). Multivariate analysis showed that age difference with index case and interventricular septum thickness were predictors for amyloid infiltration (OR=1.11, IC [1, 04–1, 19] and OR=1, 76, IC [1, 19–2, 60]). Subgroup analysis showed electroneuromyography alteration during follow up in 11 patients (delay 26.9 months, range 10–49) with statistic association with amyloid deposits (55.6 versus 7.1% when ENMG was unchanged, p<0.001) and interventricular septum thickness (p<0.010). Conclusion: Clinical and paraclinical assessment of asymptomatic carriers of ATTRv mutations shows that skin or cardiac amyloid infiltration may precede ENMG abnormalities in 16% of patients. This may trigger specific therapies in borderline cases. Age close to age of onset among index case and septum interventricular thickness appear as risk factors for developing electroneuromyogram alteration. Funding Acknowledgement: Type of funding source: None